Folk Perception of Physical Growth: A Study among the Karbis of Chagalpara and Lokhorakona Villages of Kamrup District, Assam - Dr. Chandana Deka (International Journal of Advanced Science and Technology, 2020)
Growth may be defined as a quantitative increase in size or mass. People like all animals start their life as a single cell, the fertilized ovum. Human physical growth is the product of continuous and complex interaction of heredity and environment. But there is another aspect of the terms physical growth i.e., cognitive approach. It reflects the emic view or the folk perception of growth. In this study an attempt has been made to observed the folk perception of physical growth among the people of some selected Karbi villages in the Kamrup (Metro) District, Assam.